2018
DOI: 10.1038/s41929-018-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

A Rieske oxygenase/epoxide hydrolase-catalysed reaction cascade creates oxygen heterocycles in mupirocin biosynthesis

Abstract: Oxygen heterocycles, in particular tetrahydropyrans and tetrahydrofurans, are common structural features of many biologically active polyketide natural products. Mupirocin is a clinically important antibiotic isolated from Pseudomonas fluorescens and is assembled on a tetrahydropyran ring which is essential for bioactivity. However, the biosynthesis of this moiety has remained elusive. Here we show an oxidative enzyme-catalysed cascade that generates the tetrahydropyran ring of mupirocin. A Rieske non-heme oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…3B). 14 TmlW and TmlZ from the thiomarinol gene cluster, show 55.8% and 56.3% identity, respectively, to MupW and MupZ. To investigate if the same mechanism of tetrahydropyran formation operates in both thiomarinol and mupirocin biosynthesis, TmlW was heterologously overexpressed in E. coli which is able to provide the additional redox partners and cofactors necessary to constitute an active cascade.…”
Section: Resultsmentioning
confidence: 99%
“…3B). 14 TmlW and TmlZ from the thiomarinol gene cluster, show 55.8% and 56.3% identity, respectively, to MupW and MupZ. To investigate if the same mechanism of tetrahydropyran formation operates in both thiomarinol and mupirocin biosynthesis, TmlW was heterologously overexpressed in E. coli which is able to provide the additional redox partners and cofactors necessary to constitute an active cascade.…”
Section: Resultsmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2022 epoxide formation/epoxide opening cascade starting from a non-activated alkane precursor. 110 Notably, all the other epoxidases reviewed herein use alkene precursors as substrates.…”
Section: Biosynthetic Methodsmentioning
confidence: 99%
“…Using whole-cell biotransformations, Crump, Willis and coworkers showed that the C8-C16 single bond in the acyclic precursor 198 is oxidised by the Rieske non-haem oxygenase MupW to give the corresponding 8,16-epoxide 199 ( presumably through an 8,16-alkene intermediate), which spontaneously cyclises giving a five-membered tetrahydrofuran ring product 201 (Scheme 45). 110 When both MupW and the epoxide hydrolase MupZ are included in the biotransformation system, the hydroxylated THP ring product 200 is then generated. Deletion of the mupZ gene in the mupirocin producing strain abolished production of the THP ring metabolites and the THF ring compounds were produced instead.…”
Section: Biosynthetic Methodsmentioning
confidence: 99%
“…As a first attempt to meet this need, we initially developed efficient protocols (implemented as shellscripts) and a basic PyMOL plugin (for the legacy Tkinter GUI) as Enlighten (https://github.com/marcvanderkamp/enlighten). These protocols have already been used to analyze enzyme-substrate interactions and dynamics (Rice, et al, 2019;Wang, et al, 2018) as well as for preparation for quantum mechanical / molecular mechanical (QM/MM) simulations of enzyme reactions (Byrne, et al, 2016;Drulyte, et al, 2019). Now, we introduce Enlighten2, which includes a Python package for the protocols, a new userfriendly PyMOL plugin and, notably, a Docker image with all the required software that allows seamless running of simulations on Windows, Mac and Linux operating systems without non-trivial software installation.…”
Section: Introductionmentioning
confidence: 99%